PENGUATAN PENDIDIKAN KARAKTER ANAK USIA DINI PADA BUKU KUMPULAN DONGENG PAUD KEISTIMEWAAN BINATANG - Kasmiati Kasmiati (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2019)
The results of this research are first, the early childhood book Tales Collection: Privilege of Animal presents five reinforcement of character education, namely religious, nationalist, independent, mutual cooperation, and integrity characters. Each of these characters is presented in fairy tales in the book, represented by animal figures which are be the main characters in storytelling. The five strengthening of this character education is presented in interesting fairy tales from the aspects of narration, content, and illustrations which the impact makes children love with the fairy tales of this book. This feeling of love that makes the process of strengthening character education happen. Second, the strengthening of character education is formed through the love of early childhood with the tales in this book, so that young children are enthusiastic when reading this fairytale book. This enthusiasm makes early childhood love stories in the fairy tales. This fondness then makes young children understand the contents of fairy tales, which then conditions young children to reflect, that is connecting the contents of the story and the value of characters in fairy tales with the daily life of children. From this the children then strengthened the character education of religious, nationalist, independent, mutual cooperation, and integrity in children. From here, the process of strengthening character education is formed and takes place with the media of early childhood Fairytale Book Collection: Privilege of Animals.